Pengujian Penerimaan Pengguna pada Website “Wariga” Menggunakan Metode Technology Acceptance Model (TAM) - I Ngurah Komang Agus Suryadiyatmika. S; I Gede Santi Astawa; I Gede Sri Agus Putrawan (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The "Wariga" website is an information system to determine a person's harmony condition based on the wariga framework, namely wewaran and wuku. This website has only been developed since this research was conducted. To support the development carried out towards the next stage, certain measurements can be carried out such as acceptance testing. One measure of acceptance of an information system is to use the TAM (Technology Acceptance Model) method. This research aims to assess "Wariga" using the TAM method, with the aim of obtaining information on the level of perception of each website acceptance variable. The method used in this research is a quantitative method, with the help of a questionnaire as a data collection medium. It was found that 94 respondents provided questionnaire answers for each statement submitted. The results of this research obtained a positive influence from the three TAM variables used, such as perceived comfort of 89.87%, perceived usefulness of 87.96%, and perceived acceptance of 87.83%. This shows that the “Wariga” website can be upgraded to the next stage of development.